Caracterizações molecular e imunológica parciais das proteínas rP22 e rP44 de Schistosoma mansoni e avaliação da resposta protetora na esquistossomose experimental - Cintia Martins Fagundes Rezende (2011)
Schistosomiasis remains a significant public health problem in tropical countries and it is recognized as the most important human helminth infection, in terms of morbidity and mortality. Although the existing antischistosomal drugs are highly effective, they do not prevent reinfection or granuloma formation. Therefore, vaccine strategies are essential for the control of schistosomiasis. Our group has identified the recombinant (r) P22 and (r) P44 proteins, both components of the adult worm protein fraction PIII that has been shown to engender protective and immunomodulatory effects on murine schistosomiasis. cDNA clones encoding rP22 and rP44 were isolated from a Schistosoma mansoni adult worm cDNA library using anti-PIII rabbit serum; they exhibited complete identity with S. mansoni Sm21.7 antigen and fructose 1,6-biphosphate aldolase, respectively. Immunization with the recombinant proteins rP22 and rP44, alone or together, was assayed to investigate protection against challenge infection. Mice immunized with rP22 and rP44, either alone or together, exhibited significant decrease in adult worm burden. Only mice immunized with two proteins exhibited significant decrease in hepatic eggs. Histological analysis of mice liver sections showed that either rP22- or rP22/rP44- mice vaccination produced a significant reduction in liver granuloma size and fibrosis, suggesting that rP22 might contribute to down-modulate granulomatous hypersensitivity to S. mansoni eggs. Protective immunity in mice was associated with high titers of rP22- and rP44-specific IgG antibodies; elevated production of IFN-, TNF- and IL-10; and a reduced level of IL-4. So, these findings indicate that rP22/rP44-based vaccine could be useful to elicit protection against schistosomiasis. Furthermore, the pronounced capacity of rP22 to reduce liver pathology could contribute to a more effective schistosomal vaccine. To characterize epitopes associated with antibodies produced by mice immunization with rP22 or rP44, linear B-cell epitopes from rP22 and rP44 primary sequences were predicted and 16 mer peptides were prepared by Spot synthesis. Immunoassays revealed that sera from rP22-immunized mice reacted predominantly with peptides located in the dinein light chain domain present at the C-terminal region of rP22 protein. Sera from rP44-immunized mice reacted either with peptides located at the protein surface or with those located in the TIM barrel region, a domain also known to contain amino acid residues involved in the enzymatic function of this protein. The reactivity of sera from acute, chronic and hepatosplenic S. mansoni patients to synthetic rP22- and rP44-peptides was also assayed and different patterns of reactivity were determined for each group. Comparative analysis between human sera and mice-immunized sera reactivity to rP22- and rP44-peptides showed that the most reactive peptides from either rP22 or rP44 were recognized by both vaccinated mice sera and human sera. Only peptide 2 of rP22 protein preferentially reacted to sera from rP22-vaccinated mice. In conclusion, the results described for rP22 and rP44 B-epitope mapping may prove important in the vaccine research field and provide new prospects for immunotherapy of schistosomiasis.